2004
DOI: 10.1103/physrevd.70.103520
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on isocurvature models from the WMAP first-year data

Abstract: We investigate the constraints imposed by the first-year WMAP CMB data extended to higher multipole by data from ACBAR, BOOMERANG, CBI and the VSA and by the LSS data from the 2dF galaxy redshift survey on the possible amplitude of primordial isocurvature modes. A flat universe with CDM and Λ is assumed, and the baryon, CDM (CI), and neutrino density (NID) and velocity (NIV) isocurvature modes are considered. Constraints on the allowed isocurvature contributions are established from the data for various combin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 55 publications
3
85
3
Order By: Relevance
“…This is a crucial aspect of this present work because previous analyses of correlated adiabatic and entropy (isocurvature) perturbations have always assumed power-law spectra for all the perturbations [26 -30]. When applied to the WMAP data they found that with standard priors on cosmological parameters the degree of correlation allowed is small (although see [33]). Allowing running of the spectral index, at least in the supersymmetric hybrid models we study, does not change this conclusion.…”
Section: Introductionmentioning
confidence: 86%
“…This is a crucial aspect of this present work because previous analyses of correlated adiabatic and entropy (isocurvature) perturbations have always assumed power-law spectra for all the perturbations [26 -30]. When applied to the WMAP data they found that with standard priors on cosmological parameters the degree of correlation allowed is small (although see [33]). Allowing running of the spectral index, at least in the supersymmetric hybrid models we study, does not change this conclusion.…”
Section: Introductionmentioning
confidence: 86%
“…When one considers the most general primordial perturbation, including all isocurvature modes and their correlations it becomes much harder to exclude the possibility of a significant isocurvature contribution to the CMB angular power spectrum [273]. This is mainly due to the neutrino isocurvature velocity mode and there is no theoretical model of how a scale invariant spectrum for such a mode could be generated.…”
Section: B Neutrino Isocurvature Modesmentioning
confidence: 99%
“…[34,35,36,39] and the CAMB package. The primordial adiabatic perturbation may be defined such that these correlated spectra have the opposite sign, as used in [40,41,43,44].…”
Section: Approachmentioning
confidence: 99%